GLACIAL-INTERGLACIAL CHANGES IN ORGANIC CARBON, NITROGEN AND SULFUR ACCUMULATION IN LAKE BAIKAL SEDIMENT OVER THE PAST 250 KYR - Watanabe T.; Naraoka H.; Nishimura M.; Kinoshita M.; Kawai T. (My University, 2003)
The waters of modern Lake Baikal circulate well and maintain oxic conditions for the entire lake in spite of its great depth. Past oxic/anoxic conditions in the water column are not known. Because recon- struction of paleo-redox conditions involved with climate changes provides information on dynamics of lake water circulation and biological activity, high-resolution analyses of total organic carbon (TOC), total nitrogen (TN) and total sulfur (TS) concentrations, and gamma ray density (GRD) were carried out using 492 sediment samples over the past 250 kyr (every other 1 cm from the 10 m core Ver98-1 St.5 taken from the Academician Ridge at 325 m water depth). Fifteen events of high TS/TOC ratio (>0.2 atomic) are observed; these are much larger than TS/TOC ratio of typical freshwater sediment (0.001-0.070) and also normal oxic marine sediments (0.13 in average). The sulfur occurs as pyrite by X-ray diffraction (XRD) analysis, probably being produced by sulfate-reducing bacteria (SRB). Such high TS/TOC ratios indicate high SRB activity in the lake and a high input of sulfate to the lake. A high TS/TOC layer often accompa- nies a decrease of TOC/TN ratio to ca. 5 (atomic). In particular, during a rapid cooling such as the Younger Dryas event, the TOC/TN ratio decreases steeply from 10.4 to 7.8 just prior to the increase of TS/TOC ratio from 0.02 to 0.55. Because the low TOC/TN ratio suggests low terrestrial organic matter contribution to the lake, saline water inflow from rivers could diminish to result in decreased water circulation in the lake. The rapid cooling event may restrict deep-water ventilation and create less oxic conditions in Lake Baikal.